2020
DOI: 10.1007/s00221-020-05852-5
|View full text |Cite
|
Sign up to set email alerts
|

Gravity prior in human behaviour: a perceptual or semantic phenomenon?

Abstract: Humans show a gravitational advantage in perception: we are more precise at judging the speed of downwards-moving than upwards-moving objects, indicating that gravitational acceleration is an internalised prior. However, it is unclear whether this gravity prior is based on purely perceptual cues or whether it can incorporate semantic knowledge. Previous research has used only objects which are known to comply with gravity, possibly confounding semantic and perceptual cues. Here we have addressed this question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The Weber Fractions of duration discrimination ranged between about 8% and 10%. These values are comparable to or better than those reported in previous studies involving the discrimination of duration of targets falling vertically 23 25 , despite the fact that the targets moved in the fronto-parallel plane in the previous studies while they moved in stereoscopic view in the sagittal plane in the present study. This result is somewhat surprising since it is known that looming stereomotions are generally harder to perceive than the lateral motion equivalents (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The Weber Fractions of duration discrimination ranged between about 8% and 10%. These values are comparable to or better than those reported in previous studies involving the discrimination of duration of targets falling vertically 23 25 , despite the fact that the targets moved in the fronto-parallel plane in the previous studies while they moved in stereoscopic view in the sagittal plane in the present study. This result is somewhat surprising since it is known that looming stereomotions are generally harder to perceive than the lateral motion equivalents (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…These studies found that the discrimination precision was higher when the target accelerated downwards than when it accelerated upwards, consistent with a constraint that specifies downward motion for targets accelerating under gravity. However, the results held irrespective of the specific value of gravity (Earth gravity 24 , 23 , Earth or Mars gravity 25 ) or the semantic nature of the accelerating object (ball versus rocket 23 . Since these studies only employed accelerating profiles along a linear path in the fronto-parallel plane, they could not discriminate between a representation based on internalized Newton’s laws (such as that used in target interception) and a heuristic representation based on a spatial template of the trajectory (downward motion under gravity).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Alike manual interception studies, ocular tracking experiments have shown significantly greater accuracy following target motion modeled according to natural kinematics (gravity and air drag) compared to arbitrary kinematics (hypo- or hypergravity; Diaz et al, 2013a , b ; Delle Monache et al, 2015 , 2019 ; Jörges and López-Moliner, 2019 ; Meso et al, 2020 ). Visual effects of gravity are taken into account, although with variable precision (see below), also in perceptual tasks that do not necessarily involve the production of motor response timed to the target motion, such as the discrimination of motion duration for targets shifting along the vertical (Moscatelli and Lacquaniti, 2011 ; Torok et al, 2019 ; Gallagher et al, 2020 ), time-to-passage estimation during virtual self-motion (Indovina et al, 2013a ), visuomotor synchronization (Zhou et al, 2020 ), naturalness judgments of motion under gravity (La Scaleia et al, 2014 , 2020 ; Ceccarelli et al, 2018 ), speed discrimination of targets moving in different directions (Moscatelli et al, 2019 ), and interpretation of biological motion (Chang and Troje, 2009 ; Maffei et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It might not be surprising therefore that gravity plays a substantial role in shaping our perception and behaviour. A gravitational advantage has been identified in human vision, whereby the perception of motion duration is more precise for objects falling according to gravity, versus objects moving against gravity (8)(9)(10). Eye movements are also more precise when tracking objects moving with normal gravity (1g), versus objects that move according to Weightlessness or Hypergravity (11,12).…”
Section: Introductionmentioning
confidence: 99%